Prognostic significance of primary tumor localization in stage II and III colon cancer - Sakin, Abdullah; Arici, Serdar; Secmeler, Saban; Can, Orcun; Geredeli, Caglayan; Yasar, Nurgul; Demir, Cumhur; Demir, Osman Gokhan; Cihan, Sener (BAISHIDENG PUBLISHING GROUP INC, 2018)
AIM To investigate the effects of tumor localization on disease free survival (DFS) and overall survival (OS) in patients with stage I -III colon cancer. METHODS This retrospective study included 942 patients with stage. and. colon cancer, which were followed up in our clinics between 1995 and 2017. The tumors from the caecum to splenic flexure were defined as right colon cancer (RCC) and those from splenic flexure to the sigmoid colon as left colon cancer (LCC). RESULTS The median age of the patients was 58 years (range: 19-94 years). Male patients constituted 54.2\%. The rates of RCC and LCC were 48.4\% (n = 456) and 51.6\% (n = 486), respectively. During the median follow-up of 90 mo (range: 6-252 mo), 14.6\% of patients developed recurrence and 9.1\% of patients died. In patients with stage. and. disease with or without adjuvant therapy, DFS was similar in terms of primary tumor localization (stage.

P = 0.547 and P = 0.481, respectively

stage.

P = 0.976 and P = 0.978, respectively). In patients with stage. and. disease with or without adjuvant therapy, OS was not statistically significant with respect to primary tumor localization (stage.

P = 0.381 and P = 0.947, respectively

stage.

P = 0.378 and P = 0.904, respectively). The difference between median OS of recurrent RCC (26 +/- 6.2 mo) and LCC (34 +/- 4.(mo) cases was eight months (P = 0.092). CONCLUSION Our study showed no association of tumor localization with either DFS or OS in patients with stage. or. colon cancer managed with or without adjuvant therapy. However, post-recurrence OS appeared to be worse in RCC patients.
Keywords: Colon cancer; Tumor localization; Adjuvant treatment; Overall survival; Disease free survival